If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -1)(4x + 6) = 0 Reorder the terms: (-1 + 5x)(4x + 6) = 0 Reorder the terms: (-1 + 5x)(6 + 4x) = 0 Multiply (-1 + 5x) * (6 + 4x) (-1(6 + 4x) + 5x * (6 + 4x)) = 0 ((6 * -1 + 4x * -1) + 5x * (6 + 4x)) = 0 ((-6 + -4x) + 5x * (6 + 4x)) = 0 (-6 + -4x + (6 * 5x + 4x * 5x)) = 0 (-6 + -4x + (30x + 20x2)) = 0 Combine like terms: -4x + 30x = 26x (-6 + 26x + 20x2) = 0 Solving -6 + 26x + 20x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-3 + 13x + 10x2) = 0 Factor a trinomial. 2((-3 + -2x)(1 + -5x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(1 + -5x)' equal to zero and attempt to solve: Simplifying 1 + -5x = 0 Solving 1 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5x = 0 + -1 -5x = 0 + -1 Combine like terms: 0 + -1 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2Solution
x = {-1.5, 0.2}
| -7x+3(2x-4)=-9+-4x | | 30-13y+y^2=0 | | 9n-7=5n-19 | | y^2-3y=-2 | | 1/7^2x=1/49 | | 4p=-14 | | -210+16z+2z^2=0 | | h=-16t^2+19.5t+6.5 | | -2.4y=9.6 | | 2z^2+16-210=0 | | 7x+3=2x-66 | | 6x-(5x+-1)=2 | | 0.4y=-0.8 | | y=(-2/3)x-5 | | 35(2x-1)=(x+4)+3x | | 3x-9=4+3(2x-1) | | 13(x-52)=26 | | 5y-8=15-6Y | | x+5+4x-2+3x-1=66 | | 2z/3.6 | | 75-3x=8x+2 | | (4x+8)/(x-3) | | 6x+7=107+4x | | y=dx+c | | 2+w/6=12/19 | | 3/5+2/9 | | 6x-4=4x-100 | | -144+100z^2=0 | | -1/6k+5/4=-3+4/3k | | 100.041/8 | | 7(x+3)-6=24-3x-9+10x | | 100z^2-144=0 |